2017
DOI: 10.2135/cropsci2016.07.0624
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Way Crosses vs. Single Crosses in Tobacco: First Agronomic Assessment

Abstract: In view of the increasing costs and reduced profit margins of tobacco (Nicotiana tabacum L.) production, three‐way‐cross hybrids (TWCHs) of flue‐cured tobacco were developed and examined for their potential to improve the agronomic performance and economic efficiency of the crop. Three TWCHs, each with a pair of related single‐cross hybrids (SCHs), were compared in a replicated field trial performed at two farm locations for two years for the degree of within‐population morphological variation, cured leaf yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Moreover, it was also good for ear height and ear le n gth in Melkassa (H 2 b > 50%). This indicates heritability declines from high favourable to less favourable growing environments for some of agronomic traits and shows a decrease of it from single crosses to three-way crosses [ 18 , 30 ]. If we consider only grain yield for discussion, there was a declining trend of variation for agronomic traits from high land to lowland and similar trend of variation was obtained from single crosses to three-way crosses, this might be due to the genetic mechanism of heterosis potential in single crosses than three-way crosses [ 9 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was also good for ear height and ear le n gth in Melkassa (H 2 b > 50%). This indicates heritability declines from high favourable to less favourable growing environments for some of agronomic traits and shows a decrease of it from single crosses to three-way crosses [ 18 , 30 ]. If we consider only grain yield for discussion, there was a declining trend of variation for agronomic traits from high land to lowland and similar trend of variation was obtained from single crosses to three-way crosses, this might be due to the genetic mechanism of heterosis potential in single crosses than three-way crosses [ 9 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The genotype × environment interaction was highly significant for more number of agronomic traits in the single crosses than three-way crosses indicated that the three-way crosses were more stable than single crosses similar to the previous report on sorghum [ 32 ]. This also might be due to the fact that the difference in the genetic mechanism of three-way crosses than single crosses [ 9 , 30 , 42 ]. However, as the genetic background broadness increases, the logic expects superer performance or maximum heterosis for some agronomic traits but the reality resulted in stability than increment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation